Extramedullary Spinal SOL Outcome of Surgery - Hossain, M Zahed; Hoque, Monzurul (TAJ: Journal of Teachers Association, 2010)
Spinal space occupying lesions (SOL) cause compression over the spinal cord or roots and develop myelopathy or radiculopathy and leads to Paraplegia or quadriplegia with sphincteric involvement i.e. urinary or fecal incontinence or retention. We have operated 17 cases of spinal SOL (12 were neoplastic and 5 were inflammatory i.e. tuberculous), all the patients had weakness of different grade, 0 to 4. 5 patients had urinary incontinence or retention. After operation 16 patients were improved of weakness and sphincteric function. DOI: 10.3329/taj.v22i1.5013 TAJ 2009; 22(1): 05-09